2001
DOI: 10.1055/s-2001-11388
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Synthesis of Galactosylated 1d-Chiro-Inositol and 1d-Pinitol Derivatives Using the β-Galactosidase from Bacillus circulans

Abstract: The b-D-galactosidase from Bacillus circulans regioselectively galactosylates 1D-chiro-inositol and 1D-pinitol (1D-3-Omethyl-chiro-inositol) to give mono-and digalactosylated inositols in yields of up to 45%. The enzyme does not galactosylate 1L-chiroinositol or 1L-quebrachitol (1L-2-O-methyl-chiro-inositol). This is the first report of enzymatic glycosylation of chiro-inositol and its derivatives.Oligosaccharides containing inositol sugars such as 1D-chiro-inositol (DCI) (1) and 1D-pinitol (2) are the focus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Previously, we reported that the galactosylation of 1D D -pinitol 2 by the b-galactosidase from B. circulans gave only one disaccharide product, 10, whereby galactosylation occurred on the axial position remote from the methyl group. 19 NMR spectroscopic analysis of the product mixture indicated that one of the disaccharide products was that observed previously, namely 1D D -1-O-(b-D Dgalactopyranosyl)-4-O-methyl-chiro-inositol 10. 19 A detailed analysis of the unassigned NMR correlations in the 2D-NMR spectra of the product mixture revealed that the second product was 1D D -1-O-(b-D D -galactopyranosyl)-3-O-methyl-chiro-inositol 11.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…Previously, we reported that the galactosylation of 1D D -pinitol 2 by the b-galactosidase from B. circulans gave only one disaccharide product, 10, whereby galactosylation occurred on the axial position remote from the methyl group. 19 NMR spectroscopic analysis of the product mixture indicated that one of the disaccharide products was that observed previously, namely 1D D -1-O-(b-D Dgalactopyranosyl)-4-O-methyl-chiro-inositol 10. 19 A detailed analysis of the unassigned NMR correlations in the 2D-NMR spectra of the product mixture revealed that the second product was 1D D -1-O-(b-D D -galactopyranosyl)-3-O-methyl-chiro-inositol 11.…”
Section: Introductionmentioning
confidence: 81%
“…19 NMR spectroscopic analysis of the product mixture indicated that one of the disaccharide products was that observed previously, namely 1D D -1-O-(b-D Dgalactopyranosyl)-4-O-methyl-chiro-inositol 10. 19 A detailed analysis of the unassigned NMR correlations in the 2D-NMR spectra of the product mixture revealed that the second product was 1D D -1-O-(b-D D -galactopyranosyl)-3-O-methyl-chiro-inositol 11. It is apparent that disaccharide 10 is the result of galactosylation of 2 at the axial hydroxyl position remote from that of the methyl group of 2, that is OH-6, whereas 11 is the result of galactosylation at the other axial hydroxyl of 2, OH-1, two positions removed from that of the methyl group.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations